Levels of Trimethylamine N-Oxide Remain Elevated Long Term After Left Ventricular Assist Device and Heart Transplantation and Are Independent From Measures of Inflammation and Gut Dysbiosis. (16th June 2021) - Yuzefpolskaya, Melana; Bohn, Bruno; Javaid, Azka; Mondellini, Giulio M.; Braghieri, Lorenzo; Pinsino, Alberto; Onat, Duygu; Cagliostro, Barbara; Kim, Andrea; Takeda, Koji; Naka, Yoshifumi; Farr, Maryjane; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Trimethylamine N-oxide (TMAO)—a gut-derived metabolite—is elevated in heart failure (HF) and linked to poor prognosis. We investigated variations in TMAO in HF, left ventricular assist device (LVAD), and heart transplant (HT) and assessed its relation with inflammation, endotoxemia, oxidative stress, and gut dysbiosis. Methods: We enrolled 341 patients. TMAO, CRP (C-reactive protein), IL (interleukin)-6, TNF-α (tumor necrosis factor alpha), ET-1 (endothelin-1), adiponectin, lipopolysaccharide, soluble CD14, and isoprostane were measured in 611 blood samples in HF (New York Heart Association class I–IV) and at multiple time points post-LVAD and post-HT. Gut microbiota were assessed via 16S rRNA sequencing among 327 stool samples. Multivariable regression models were used to assess the relationship between TMAO and (1) New York Heart Association class; (2) pre- versus post-LVAD or post-HT; (3) biomarkers of inflammation, endotoxemia, oxidative stress, and microbial diversity. Results: ln-TMAO was lower among HF New York Heart Association class I (1.23 [95% CI, 0.52–1.94] µM) versus either class II, III, or IV (1.99 [95% CI, 1.68–2.30], 1.97 [95% CI, 1.71–2.24], and 2.09 [95% CI, 1.83–2.34] µM, respectively; all P <0.05). In comparison to class II–IV, ln-TMAO was lower 1 month post-LVAD (1.58 [95% CI, 1.32–1.83] µM) and 1 week and 1 month post-HT (0.97 [95% CI, 0.60–1.35] and 1.36 [95% CI, 1.01–1.70] µM). ln-TMAO levels in long-term LVAD (>6 months: 1.99 [95% CI, 1.76–2.22] µM) and HT (>6 months: 1.86 [95% CI, 1.66–2.05] µM) were not different from symptomatic HF. After multivariable adjustments, TMAO was not associated with biomarkers of inflammation, endotoxemia, oxidative stress, or microbial diversity. Conclusions: TMAO levels are increased in symptomatic HF patients and remain elevated long term after LVAD and HT. TMAO levels were independent from measures of inflammation, endotoxemia, oxidative stress, and gut dysbiosis.